Germ line transmission of an inactive N-myc allele generated by homologous recombination in mouse embryonic stem cells. - Stanton, B R (1990)
We have disrupted one allele of the N-myc locus in mouse embryonic stem (ES) cells by using homologous recombination techniques and have obtained germ line transmission of null N-myc ES cell lines with transmission of the null N-myc allele to the offspring. The creation of mice with a deficient N-myc allele will allow the generation of offspring bearing null N-myc alleles in both chromosomes and permit study of the role that this proto-oncogene plays in embryonic development.